Pregnancy-related acquired hemophilia A initially manifesting as pleural hemorrhage: A case report. Issue 3 (January 2019) - Qian, Lili; Ge, Hangping; Hu, Pingping; Zhu, Ni; Chen, Junfa; Shen, Jianping; Zhang, Yu
Abstract: Rationale: Acquired hemophilia A is a rare hemorrhagic disease in which the body produces specific antibodies that attack factor VIII, resulting in bleeding that is mainly mucocutaneous and associated with soft tissue and the gastrointestinal system. Approximately 50% of this disease derives from basic diseases, such as autoimmune diseases, cancer, and pregnancy. Patient concerns: We report a 35-year-old postpartum female with acquired hemophilia A who initially presented with pleural hemorrhage. Diagnoses: In this patient activated prothrombin time (PT) and activated partial thromboplastin time (APTT) were found, and the factor VIII activity was 12.6%, furthermore Bethesda assay showed a FVIII antibody titer of 7.4 Bethesda units (BUs). Interventions: The treatment requires a 2-pronged approach: treatment of the bleeding and elimination of the inhibitor. Outcomes: After hemostatic agents were used and inhibitors were eradicated, the patient achieved complete remission without relapse. Lessons: It is essential to recognize the development of disease earlier in pregnant woman.